Correlation of impaired tear mucin production with relative expression of neurtrophil activation marker CD 15+ in patients with type 2 diabetes mellitus (Ukrainian Journal of Ophthalmology, 2025)
Aim: To determine tear mucin levels in patients with type 2 diabetes mellitus (T2DM) and correlate them with the levels of the neutrophil activation marker CD15+ in epithelial cells of the bulbar conjunctiva in patients with T2DM, depending on the grades of squamous metaplasia.Material and Methods: Thirty-seven patients (37 eyes) with ocular surface damage and T2DM comorbidity were enrolled in this study. Fifteen sex- and age-matched participants without T2DM comprised the control group. Based on the cytological changes in the bulbar conjunctiva and according to Nelson’s classification, patients with T2DM were divided into two main groups: Study group 1 – 29 patients (29 eyes) with changes in the bulbar conjunctiva corresponding to grades II and III of squamous metaplasia according to Nelson’s classification; study group 2 – 8 patients (8 eyes) with grades 0-I according to Nelson’s classification. Results: The mucin level was significantly lower in study group I - 0.95 ± 0.18 g/l compared to study group II - 1.28 ± 0.09 g/l and controls - 1.59 ± 0.08 g/l (p
Keywords: mucin; CD15+; ocular surface damage; DED; inflammation; T2DM; diabetes mellitus; cornea